Nilai-nilai Pendidikan dari Kisah Haditsul Ifki dalam Q.S. An-Nur Ayat 11-20 tentang Sikap Tabayyun dan Kehati-hatian Menerima Berita di Era Teknologi Informasi - Jati Wahyuni (Jurnal Pendidikan Islam Indonesia, 2019)
In the era of information technology today, cyberspace comes as the second world for society. The One of negative effects of this is the occurrence of conflict because of hoax. Muslims are reminded to do not be easy to believe in the unbelievable news. This can be seen from an event known as Haditsul Ifki which occurred in the time of the prophet and enshrined in the Qur'an, Surah An-Nur verse 11-20. The method used in this research was a method of descriptive analysis with a library research by collecting data relating to the discussion. The results of this research were to find a way for a Muslim to avoid the negative effects of hoax. The conclusion is a Muslim must has a tawaqquf (refraining from directly accept or reject news), tabayyun (looking for proof or truth), tajannub al-zhann (avoiding prejudice), husnuz zhan (good prejudice) and avoiding hate speech to avoid the negative effects of hoax.